Assessment of pubertal development in juvenile male rats after sub-acute exposure to bisphenol A and nonylphenol - Tan, B.L.L.; Kassim, N.M.; Mohd, M.A. (2003)
The effects of bisphenol A and nonylphenol on pubertal development in the intact juvenile/peripubertal male Sprague-Dawley rats was observed in this study from PND23-52/53. Two groups of rats were administered orally with either 100 mg/kg body weight of nonylphenol or bisphenol A. Another group of rats were administered orally with a mixture of 100 mg/kg body weight of nonylphenol and bisphenol A. Control group was administered with the vehicle of Tween-80 with corn oil (1:9 v/v). Observations made in this study included growth, age at preputial separation, thyroid, liver, testis and kidney weight and histology, epididymal and seminal vesicle plus coagulation gland weight. Nonylphenol and bisphenol A have been observed to cause delay in puberty onset as well as testicular damage in the treatment groups when compared to the control; spermatogenesis was affected in most treated rats. Bisphenol A also caused the enlargement of the kidney and hydronephrosis. Administration of nonylphenol and bisphenol A as a mixture has caused less than additive effects. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.